Impact of trade liberalisation on Ghana's agricultural sector - Abdul Majeed Seidu; Aleksandar Vasilev (Economics and Econometrics Research Institute (EERI), 2024)
The study sought to analyse the impact of trade liberalization on Ghana's agricultural sector. This study's research design, which is secondary quantitative, was chosen. The study used econometric methods such as multivariate regression analysis, Bounds test etc to analyse the data. According to the study's findings, trade liberalization which comprises of flexible exchange rate (REXR), Export and Import price ratio (EP/IP), Agricultural Capital Formation (ACF), Foreign Investment in Agricultural Sector (FIA) and Agricultural Degree of Openness (ADO) haven't really improved agricultural performance in Ghana from 1993-2022. In contrast, globalization has favourably impacted technology, infrastructural development, growth, and living standards in other developing Asian nations including India, China, Lebanon etc through the promotion of foreign direct investments (Siddiqui and Ahmed, 2017). Due to the limited absorption of technology, poor infrastructure and overdependence on other countries in Ghana, globalization may not have an impact on sustainable agriculture. The negative interactions between Ghanaian Agricultural performance, Agricultural exports and imports price ratio, Real Exchange Rate, might have accounted for Ghana's continuous decline in agriculture performance instead of having a positive impact
Keywords: F10; 330; agriculture; trade liberalization; real exchange rat